Long term outdoor performance evaluation of printed semitransparent organic photovoltaic modules for BIPV/BAPV applications - Feroze, Sarmad; Distler, Andreas; Dong, Lirong; Wagner, Michael; Channa, Iftikhar Ahmed; Hoga, Felix; Brabec, Christoph; Egelhaaf, Hans-Joachim (Energy and Environmental Science, 2024)
Recently, organic photovoltaics (OPV) have achieved power conversion efficiencies (PCE) above 20% thus coming closer to market entry. Building-integrated photovoltaics (BIPV) and building-attached photovoltaics (BAPV) are two key areas where the functional advantages of both OPV and BIPV/BAPV complement each other and thus could pave the way for market penetration of OPV. Herein, we report on large-area, all-solution-processed flexible OPV modules manufactured by a fully roll-to-roll (R2R) method with high levels of process repeatability. The OPV modules show an accelerated lifetime (ALT) of more than 1000 h and 2800 h under the ISOS-L2 and ISOS-D3 testing conditions, respectively. Long-term outdoor monitoring of the OPV modules was conducted in a typical central European climate, considering two distinct mounting angles that hold significant relevance for BIPV installations i.e., 45° inclination with respect to the ground (representing the optimal tilt angle of the site) and 90° vertical mounting (as mostly encountered in BIPV façades). The ISOS-O2 protocol was used as the test standard for outdoor monitoring. The results show that the OPV modules can offer higher daily specific energy yields (YFD), i.e., higher ratios of daily energy yield and STC WP capacity of the module, than a reference mono-crystalline (m-Si) module for BIPV installations typical of a rooftop case (i.e., 45°), whereas for façade integrated cases (i.e., 90°), OPV modules offer YFD values identical to that of m-Si modules. Detailed laboratory investigations reveal that the higher YFD values of the OPV modules at 45° mounting stems from their negligible temperature coefficient of −0.008% °C−1, whereas at 90° mounting, the angle-dependent response of the modules plays a crucial role.
CRIS-Team Scopus Importer:2025-02-04